Resolution of Default in Fiduciary Guarantee Agreements : An Empirical Study at Bank Syariah Indonesia Area Meulaboh - Cut Sarah Maulida; Darmawan Darmawan; Suhaimi Suhaimi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Based on Article 1338 paragraph (1) of the Indonesian Civil Code, “every legally executed agreement shall bind the parties as law.” This provision implies that every agreement carries binding legal force equivalent to legislation for the parties involved and therefore must be fulfilled in accordance with the terms mutually agreed upon, including fiduciary guarantee agreements. Nevertheless, in practice, there are still debtors who fail to perform their contractual obligations, particularly by neglecting to pay the financing installments that have been previously agreed upon. This study employed an empirical juridical research method. The data were collected through primary data obtained from field research and secondary data derived from library research. A qualitative approach was applied in analyzing the data, while the research findings were presented descriptively. The findings reveal that the settlement of defaults at Bank Syariah Indonesia Area Meulaboh prioritizes non-litigation mechanisms. The bank generally offers alternative resolutions in the form of voluntary sales and voluntary surrender of the collateral object. In such cases, the debtor is required to sign a written statement confirming consent for the fiduciary collateral to be further processed and sold in order to settle the debtor’s outstanding obligations. This study suggests that banks should reassess the collectibility history of prospective customers from previous financing activities to minimize the risk of non-performing financing in the future. In addition, banks are encouraged to implement more flexible restructuring policies that are tailored to the debtor’s financial circumstances and income conditions. Furthermore, clearer and more comprehensive regulations concerning default settlement are necessary to ensure adequate protection for debtors, particularly during unstable economic conditions, while simultaneously safeguarding the interests of banks as financing institutions.